Tangled up in blue : policing the American city - Brooks, Rosa (New York : Penguin Press, 2021)
"Journalist and law professor Rosa Brooks goes beyond the "blue wall of silence" in this radical inside examination of American policing" -- Amazon.com.
"A radical inside examination of policing in modern America, from a Georgetown University law professor turned reserve police officer"--
In 2015, against the advice of everyone she knew, Brooks applied to become a sworn, armed reserve police officer with the Washington, DC, Metropolitan Police Department. The Black Lives Matter movement was gaining momentum, protests wracked America's cities, and each day brought more stories of cruel, corrupt cops, police violence, and the racial disparities that mar our criminal justice system. In the poorest, most crime-ridden neighborhoods of the nation's capital, Brooks found a reality far more complex than the headlines suggested. In a nation increasingly divided by race, class, ethnicity, geography, and ideology, she argues that a truly transformative approach to policing requires us to move beyond sound bites, slogans, and stereotypes. -- adapted from jacket
Because it was there -- The Academy -- The street -- Epilogue.
Includes bibliographical references (pages 355-367).
108665
Keywords: Police -- Washington (D.C.); Law enforcement -- Washington (D.C.); Criminal justice, Administration of -- Washington (D.C.); Sociology; Washington (D.C.)